Team leadership in high-hazard environments performance, safety and risk management strategies for operational teams - Cadieux, Randy E. (Gower, 2014)
Safety performance is a complicated issue, particularly in high-hazard environments, where time and other constraints, as well as impacts can be exaggerated. From an organizational and business perspective, safety and production/performance are often seen as competing goals.